THE CONTRIBUTION OF SOCIAL MEDIA LIVE STREAMING TO INCREASING IN SALES FOR SMES IN SOLO RAYA - Ahmad Aufar Ribhi; Mohamad Rifqy Roosdhani; Imam Syafii (Bajang Institute, 2023)
In the increasingly advanced digital era, digital marketing has become one of the most effective and affordable marketing strategies for businesses. It has become a crucial element in modern marketing strategies to enhance consumer engagement and boost sales. One of the most widely used digital marketing platforms by Micro, Small, and Medium Enterprises (MSMEs) today is through social media channels such as Instagram, Facebook, and TikTok, utilizing the Live Stream feature where consumers can interact directly with sellers. With Social Media Live Streaming, MSMEs can expand their market reach and interact directly with customers, thereby positively impacting sales. Therefore, the aim of this research is to analyze how effective and significant the contribution of Social Media Live Streaming is in increasing sales and profits for Micro, Small, and Medium Enterprises. The research method employed in this study is qualitative, where data was collected through careful observation. This approach involved detailed descriptions within a deep context, complemented by notes from interviews, as well as the analysis of records and documents. The results of this research indicate that the use of live streaming on social media does not have a significant impact on increasing sales for SMEs in Solo Raya